Chronic antepartum maternal hyperoxygenation in a case of severe fetal Ebstein's anomaly with circular shunt physiology - Arunamata, Alisa (Ann Pediatr Cardiol, 2017)
Perinatal mortality remains high among fetuses diagnosed with Ebstein's anomaly of the tricuspid valve. The subgroup of patients with pulmonary valve regurgitation is at particularly high risk. In the setting of pulmonary valve regurgitation, early constriction of the ductus arteriosus may be a novel perinatal management strategy to reduce systemic steal resulting from circular shunt physiology. We report the use of chronic antepartum maternal oxygen therapy for constriction of the fetal ductus arteriosus and modulation of fetal pulmonary vascular resistance in a late presentation of Ebstein's anomaly with severe tricuspid valve regurgitation, reversal of flow in the ductus arteriosus, and continuous pulmonary valve regurgitation.